Directional Energy Transfer in Nanocrystals of [Ru(2, 2′‐bipyridine)3][NaCr(oxalate)3]. Issue 13 (14th December 2015) - Previtera, Elia; Tissot, Antoine; Hauser, Andreas
Abstract: Size‐controlled nanocrystals (140 and 670 nm) and microcrystals (2.5 μm) of the three‐dimensional oxalate network [Ru(bpy)3 ][NaCr(ox)3 ] (ox = oxalate, bpy = 2, 2′‐bipyridine) were prepared by the reverse micelle technique. The photophysical properties of the [Cr(ox)3 ] 3– chromophores in the nanocrystals at low temperatures are significantly different from those of the same chromophore in 4 μm crystallites prepared by fast precipitation. For the latter, the absorption in the region of the R lines of the 4 A2 → 2 E transition is characterized by a sharp doublet. For the nanocrystals, the inhomogeneous broadening of the two lines is considerably larger and they have tails on the low‐energy side. The 4 μm crystallites at low temperatures show equally sharp emission from the R1 line, whereas the emission intensity from the nanocrystallites is shifted into the low‐energy tail. Time‐resolved fluorescence line‐narrowing spectra and luminescence decay curves demonstrate that this is due to efficient directional energy migration from the center of the nanocrystals towards the surface. Abstract : The complex sequence of events from the first energy‐transfer step in [Ru(bpy)3 ][NaCr(ox)3 ] (bpy = 2, 2‐bipyridine, ox = oxalate) nanocrystals after the initial excitation of [Ru(bpy)3 ] 2+ as sensitizer to [Cr(ox)3 ] 3– in the core of nanocrystals to directional energy migration within the 2 E state to the surface chromophores is elucidated.